2020
DOI: 10.1002/ijgo.13236
|View full text |Cite
|
Sign up to set email alerts
|

Update on clinical outcomes of women with COVID‐19 during pregnancy

Abstract: Most women with COVID‐19 delivered at or beyond the late preterm period. Some who delivered prematurely had other medical indications for preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 6 publications
0
19
0
8
Order By: Relevance
“…Eight studies (95 247 women) compared pregnant populations with non-pregnant populations,2526272829303132 and four studies (2230 women) compared pregnant women with covid-19 versus pregnant women without covid-19 33343536. Forty cohort studies reported on clinical manifestations (13 018 pregnant, 85 084 non-pregnant women),25262728293031323536373839404142434445464748495051525354555657585960616263646566 45 studies reported on covid-19 related maternal outcomes (14 094 pregnant, 85 169 non-pregnant women),2526272829303132353637383940414243454647484950515354555657585961626364656667…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (95 247 women) compared pregnant populations with non-pregnant populations,2526272829303132 and four studies (2230 women) compared pregnant women with covid-19 versus pregnant women without covid-19 33343536. Forty cohort studies reported on clinical manifestations (13 018 pregnant, 85 084 non-pregnant women),25262728293031323536373839404142434445464748495051525354555657585960616263646566 45 studies reported on covid-19 related maternal outcomes (14 094 pregnant, 85 169 non-pregnant women),2526272829303132353637383940414243454647484950515354555657585961626364656667…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 2 studies were excluded due to duplicity of data reporting. Out of 27 studies [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ], 16 studies were from China (14 were from Hubei province and 2 from Guangzhou) and 4 studies was from USA [ [44] , [45] , [46] , [47] ], 2 from France [ 48 , 49 ], 2 from Italy [ 50 , 51 ], 1 from UK [ 52 ], 1 from Spain [ 53 ], and 1 from Iran [ 54 ]. Of 27 studies, 4 studies (n = 233) also included a control group [ [38] , [39] , [40] , [41] ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a substantial reduction in the heterogeneity measure was observed for adverse pregnancy outcomes when the analysis was restricted to studies ascertaining pregnancy outcomes with a sample size greater than 10 ( Table 3 ). In the sensitivity analysis after restricting the analysis to relatively large Chinese studies [ 28 , 32 , [35] , [36] , [37] , [38] , [39] , [40] , 43 ], removing a US study due to relatively a low sample size [ 45 ] and two European studies due to relatively a small sample size [ 52 ] and a large number of women without pregnancy status [ 49 ], the heterogeneity was eliminated for all pregnancy outcomes. After removing heterogeneity, the rate of C-section was substantially higher in Chinese studies (91 %, I 2 = 9.2 %) compared to the US (40 %, I 2 = 0 %) or European (38 %, I 2 = 9.3 %) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, viral antigens are engulfed by dendritic cells, which migrate to lymph nodes and initiate acquired responses by resident CD4 and CD8 T cells ( Littauer and Skountzou, 2018 ). Consequently, pregnant women are potentially more susceptible to severe viral infections due to a shift from cellular to humoral immunity, with a decrease in cellular immunity and an increase in humoral immunity during pregnancy and puerperium ( Kourtis et al, 2014 ; Zeng et al, 2020 ). Indeed, published articles on influenza A virus subtype H1N1 or circulating rhinovirus strains in healthy pregnant women indicated significantly reduced IFN responses, suggesting that there is an increased vulnerability to severe viral infection outcomes during pregnancy ( Littauer and Skountzou, 2018 ).…”
Section: Introductionmentioning
confidence: 99%